Haemoglobin and C-reactive protein levels are efficient at identifying neoplasms as the most common early mortality of chronic diseases in emergency department patients - Mantorski, Wawrzyniec; Feusette, Piotr; Tukiendorf, Andrzej; Wolny-Rokicka, Edyta Idalia (Contemporary Oncology/Współczesna Onkologia, 2023)
Extensive research has focused on emergency department (ED) and post-admission deaths, seeking to understand their frequency and causative factors. With the rising prevalence of advanced diseases, it is crucial to identify patients in need of end-of-life care and ensure its high quality. In this epidemiological study, we analyse routine ED blood tests to identify early warning signs of deteriorating patients with common non-traumatic and non-infectious (chronic) conditions. Material and methods: We conducted a retrospective single-centre study for the years 2016–2019 using medical records and electronic data from the Multi-Specialistic Hospital in Gorzów Wielkopolski, Poland. We examined 8971 unique patients with circulatory, neoplastic, and endocrine diseases. We assessed the impact of 2 grouping variables (survivors and non-survivors) on a continuous outcome variable, including age and 37 routine blood tests. Results: Two-way analysis of variance revealed that haemoglobin (Hb), haematocrit (Hct), and C-reactive protein (CRP) are the best differentiating biomarkers for early death in ED patients with cardiovascular, oncological, and endocrine diseases (excluding Hct due to its strong correlation with Hb). The Marczewski-Steinhaus taxonomy highlighted that oncological patients had the shortest survival time, averaging just 2 days from admission among ED non-survivors. Conclusions: Among routinely tested ED biomarkers, Hb and CRP levels are efficient at identifying neoplasms as the most common early mortality of chronic diseases in ED patients.